Tourism planning and policy - Dredge, Dianne; Jenkins, John (Australia, 2007)
Informed tourism policy and planning is born of creative, strategic and resourceful individuals and agencies. It requires strong research, analytical and technical skills, and is based on an appreciation of theoretical frameworks concepts, methods and approaches. On a practical level, it requires political and highly tourism planning practitioners and researchers with extensive national and international experience, we believe that, on the whole, tourism policy and planning does not receive the critical attention it deserves. It is frequently seen as an outcome, an afterthought or a set of implications arising from tourism research. There is much talk about the policy implications of the impact of tourism or the need for government action to enhance the economic contribu tions of tourism. How the actions of governments, existing policy positions and policy-making processes contribute to these issues is often sidelined. With this book, Tourism Planning and Policy, we seek to promote critical and informed reflection of the way policy is made, the complex nature of tourism policy problems and issues, and the ideological and practical influences on tourism policy development.
Keywords: Tourism - Australia; Tourism - Australia - Planning; Tourism - Government Policy - Australia